Determinación de contaminantes físicos en el proceso de elaboración de panela granulada, en la parroquia de Palo Quemado del cantón Sigchos. - Jiménez Aguilar, Samuel Alejandro (2023)
The main objective of this research was the determination of physical contaminants in the process of elaboration of granulated panela, through the application of the check list used to make the diagnosis of the current situation of the farms of the parish, where the presence of contaminants such as insects, flies, mosquitoes, ants and pieces of piolas coming from the shelling machines was evidenced, as well as the presence of filings in the utensils such as the sifters, which is given because the producers do it in a traditional way, In addition, there is no control and management of the processing of this product due to the lack of knowledge of the associated producers, which has led to the distribution of a product that is not innocuous and does not meet the necessary characteristics demanded, which has caused a great economic loss to the associates and the collection center that make up the parish. In view of this, a diagnostic study was carried out on 5 associated farms, taking into consideration 4 aspects to be evaluated: facilities, equipment and utensils, hygiene practices and protective equipment, and production operations. According to the results obtained in the diagnosis, the farms do not have adequate facilities, nor is there a distribution and cleaning of the areas that make up the mill; 2 of the 5 mills have equipment and utensils made improvised with rubber and plastic trays, nor do they have a cleaning and disinfection plan; the floor of the facilities are not covered with cement, they are made of earth; the roof structure of the facilities are made of wood, which causes detachments that can fall on the product; There are sections of the roof and windows that are not completely covered with mesh, which allows insects to enter the interior; production personnel do not have PPE and proper hygiene practices such as hand washing; there is no physical delimitation between production areas, which creates a risk of cross-contamination; and there is no quality control, which is why the final product contains these contaminating residues. With these and other deficiencies detected on the farms, corrective actions were taken that will allow the associated producers to correct their current deficiencies in their facilities and to be able to apply them in the future. In addition, based on the corrective actions, an operating manual was prepared, which took into account the four aspects that were evaluated in the diagnosis, establishing minimum operating procedures that the facilities must comply with as measures to guarantee product quality. A magnetic grill made up of 5 neodymium magnets and stainless-steel plates was also designed to extract metal particles. The tests carried out with these neodymium magnets were able to extract galvanized metal residues, black metal, metal used to make welding electrodes (tungsten), screws, bolts, wires and iron filings, but it was not possible to extract stainless steel and copper metals. The estimated cost for this magnetic grill is $288.10, also a cost/benefit analysis was made to invest in this instrument, detailing the benefits if this instrument is acquired.